Measuring the Total and Sequestered Organic Matter Contents of Grassland and Forest Soil Profiles in the National Ecological Observatory Network Initiative. Issue 6 (3rd December 2015) - Ghabbour, Elham A.; Davies, Geoffrey; Sayeed, Abeer A.; Croman, Millicent T.; Hoehing, Brittney A.; Ayres, Edward
Abstract : The National Soil Project (NSP) at Northeastern University has been measuring the total and sequestered soil organic matter (SOM) contents of more than 2000 soil horizons from all 50 US states since 2008. The sequestration data establish a baseline SOM content of a soil and are a measure of its quality and health. In this paper, on behalf of the National Ecological Observatory Network (NEON)–NSP collaboration we report the total and sequestered SOM contents of 11 grassland and forest profiles in eight US states at elevations of 25 to 1548 m and 7 soil orders to depths of 200 cm. Such soils serve (i) as standards with which other soils can be compared and (ii) as benchmarks for NEON measurements. Total SOM was measured by optimized loss‐on‐ignition (LOI) of dried soil samples at 650°C for 12 h. Sequestered SOM is represented by long‐lived humic substances (HS) in the form of humic acids (HA), fulvic acids (FA), and sequestered dissolved organic carbon (DOC). Humic acids were measured gravimetrically; FA and sequestered DOC were measured by visible and UV spectrophotometry, respectively. Major findings are: (i) the data are mostly reproducible; (ii) carbon sequestration drops sharply below the A horizons; (iii) there are three profile types (in six Type A profiles the percentage HA exhibits a minimum with increasing depth, whereas no minimum is evident in the four Type B profiles investigated, and the Jornada profile labeled C features increasing percentage HA with increasing depth due to a carbonate barrier at 78 cm depth); (iv) decreasing FA/HA ratios with increasing percentage humification indicates FA as precursors of HA; (v) regression of FA against HA for all Type B profiles has a slope of 0.38 (cf. 0.29 for Maine profiles) and is a measure of the sequestration status of those soils; and (vi) HA in four of the profiles retain about three times more water than their total SOM, as observed previously for soil profiles in northern Maine.